Risk of tumor transmission after thoracic allograft transplantation from adult donors with central nervous system neoplasm—A UNOS database study. Issue 4 (2nd March 2017) - Hynes, Conor F.; Ramakrishnan, Karthik; Alfares, Fahad A.; Endicott, Kendal M.; Hammond‐Jack, Katrina; Zurakowski, David; Jonas, Richard A.; Nath, Dilip S.
Abstract: Background: We analyzed the UNOS database to better define the risk of transmission of central nervous system (CNS) tumors from donors to adult recipients of thoracic organs. Methods: Data were procured from the Standard Transplant Analysis and Research dataset files. Donors with CNS tumors were identified, and recipients from these donors comprised the study group (Group I). The remaining recipients of organs from donors who did not have CNS tumors formed the control group (Group II). Incidence of recipient CNS tumors, donor‐related malignancies, and overall survival were calculated and compared in addition to multivariable logistic regression. Results: A cohort of 58 314 adult thoracic organ recipients were included, of which 337 received organs from donors who had documented CNS tumors (Group I). None of these recipients developed CNS tumors at a median follow‐up of 72 months (IR: 30‐130 months). Although overall mortality in terms of the percentage was higher in Group I than Group II (163/320=51% vs 22 123/52 691=42%), Kaplan‐Meier curves indicate no significant difference in the time to death between the two groups ( P =.92). Conclusions: There is little risk of transmission of the common nonaggressive CNS tumors to recipients of thoracic organs.